Are asthma patients at increased risk of clinical depression? A longitudinal cohort study. (2nd January 2016) - van den Bemt, Lisette; Luijks, Hilde; Bor, Hans; Termeer, Evelien; Lucassen, Peter; Schermer, Tjard
Abstract: Objective : In this study, we assessed whether adult patients with asthma are more likely to be diagnosed with depression than diabetes patients or "healthy" controls during follow-up in primary care. Methods : Data from the Nijmegen Continuous Morbidity Registration were used to assess the risk for a first depression. Patients with asthma were compared with patients with diabetes and with two healthy controls matched on age, gender, socioeconomic status and attending general practice. With Cox proportional hazard analysis, we compared the risk of depression between these groups. These analyses were corrected for relevant covariates including a time-depending variable for multimorbidity. Explorative subgroup analyses were done for age, gender, socioeconomic status and multimorbidity. Results : Cumulative incidence of depression in asthma patients was 5.2%, in DM patients 4.1% and in control subjects 3.3%. The hazard ratios for a first episode of depression in the asthma patients ( n = 795) compared to DM patients ( n = 1033) and control subjects after correction for covariates were 1.11 (95% CI 0.60–2.04) and 1.18 (95% CI 0.78–1.79), respectively. Exploratory analyses showed that asthma patients without multimorbidity were at higher risk for a depression compared to reference groups, while asthma patients with multimorbidity were at lower risk for depression. Conclusion : Asthma patients were not more likely to be diagnosed with a first depression compared to "healthy" control subjects or diabetes patients. The influence of multimorbidity on depression risk in asthma patients warrants further study.